A case report of delayed persistent third-degree atrioventricular block 7 years after eccentric umbrella occlusion of a perimembranous ventricular septal defect in infancy - Wei, Lihui; Zeng, Decai; Huang, Liuliu; Luo, Xiangjie; Wu, Ji (Frontiers in Pediatrics, 2025)
This article reports an 8-year-old female patient who underwent trans-thoracic small-incision interventional Pm-VSD occlusion with an eccentric umbrella (defect diameter 10 mm, occluder waist diameter 12 mm) at 4 months of age (July 2017). Seven years after the operation (October 2024), she gradually developed third-degree atrioventricular block. Despite the removal of the occluder and ventricular septal defect repair combined with steroid pulse therapy, the conduction abnormality persisted. This case, with a 7 - year disease course evolution, provides in - depth insights into the development process of delayed complete atrioventricular block (CAVB) following eccentric umbrella occlusion in infancy and early childhood, particularly for high - risk patients with occlusion adjacent to the conduction system. It also suggests the significance of electrocardiogram monitoring for over 5 years post - operation in such high - risk patients.